Annual Plan 2000-2001 Part I - Plan in Outline - Analysis of Sectoral Outlays and Statistical Statements Government of Goa - Planning Commission (Planning Commission, 2000)
The net sown area in the State is 146010 Ha. which forms 40.43 per cent of total geographical area of 361113 Ha. of this, 25158 ha. area is cultivated twice. Important crops of the State are paddy, cashewnut and coconut. Paddy forms about 32.97 cent of gross cropped area followed by cashewnut 30.89 per cent and coconut 14.5 per cent. Remaining gross cropped area is under arecanut, garden crops, vegetables, cereals, millets/pulses and oilseeds. An area of 125473 Ha.(34.7 %) of the geographical area is estimated to be under forest Waste land is estimated to be about 59066 Ha.
Directorate of Planning, Statistics and Evaluation, Government of Goa